Fabrication of microgrooves with secondary microstructures by electrical discharge machining using a functionally graded laminated electrode. (30th November 2020) - Zhou, Zhiwen; Wu, Xiaoyu; Lei, Jianguo; Hu, Zuohuan; Gao, Guoli; Tang, Yong; Chang, Chuntao
Abstract: As tool electrodes of different materials have distinct electrical discharge machining (EDM) wear rates, this paper proposed a method for fabricating a surface microstructure by EDM with a laminated electrode including a functionally graded material foil. The preparation of functionally graded CuSn foils and the formation of a functionally graded laminated electrode (FGLE) were studied. Additionally, the effects of the electrical parameters and thermal diffusion temperature on the EDM results were explored. The experimental results show that after treatment with thermal diffusion at a temperature of 500 °C for 10 h, a Sn-plated Cu foil was transformed into a functionally graded CuSn foil in which the distribution of Sn was helpful to the generation of a secondary microstructure on the workpiece. After four rounds of wear-variation EDM with positive polarity under a machining voltage 200 V, a pulse width 1 μ s, and a pulse interval 10 μ s, a FGLE blank made of functionally graded CuSn foil and Cu foils produced a stable working surface profile. Based on the optimized process parameters, a microgroove array, a width of 370 μ m and a depth of 360 μ m, and complex surface microstructures were fabricated on the #304 stainless steel workpieces, each microgroove has a 75 μ m high secondary microstructure.